La fin de vie anticipée - Valérie Depadt (Droit et Cultures, 2018)
Since the early 2000s, one of the legislator’s priorities has been to respect the patient’s will, even if the patient is no longer able to express it. How can we take into account the will of a person who is no longer able to express it? The purpose of anticipatory measures is to provide an answer to this question. Thus, various instruments coexist in our legal landscape in order to allow people to arrange their future in the case that they are no longer able to govern their own lives and to look after their interests alone: the mandate for future protection, the designation of a person of trust and advance directives.